Longitudinal growth and morphology of the hippocampus through childhood: Impact of prematurity and implications for memory and learning. Issue 8 (12th February 2014) - Thompson, Deanne K.; Omizzolo, Cristina; Adamson, Christopher; Lee, Katherine J.; Stargatt, Robyn; Egan, Gary F.; Doyle, Lex W.; Inder, Terrie E.; Anderson, Peter J.
Abstract: The effects of prematurity on hippocampal development through early childhood are largely unknown. The aims of this study were to (1) compare the shape of the very preterm (VPT) hippocampus to that of full‐term (FT) children at 7 years of age, and determine if hippocampal shape is associated with memory and learning impairment in VPT children, (2) compare change in shape and volume of the hippocampi from term‐equivalent to 7 years of age between VPT and FT children, and determine if development of the hippocampi over time predicts memory and learning impairment in VPT children. T 1 and T 2 magnetic resonance images were acquired at both term equivalent and 7 years of age in 125 VPT and 25 FT children. Hippocampi were manually segmented and shape was characterized by boundary point distribution models at both time‐points. Memory and learning outcomes were measured at 7 years of age. The VPT group demonstrated less hippocampal infolding than the FT group at 7 years. Hippocampal growth between infancy and 7 years was less in the VPT compared with the FT group, but the change in shape was similar between groups. There was little evidence that the measures of hippocampal development were related to memory and learning impairments in the VPT group. This study suggests that the developmental trajectory of the human hippocampus is altered in VPT children, but this does not predict memory and learning impairment. Further research is required to elucidate the mechanisms for memory and learning difficulties in VPT children. Hum Brain Mapp 35:4129–4139, 2014 . © 2014 Wiley Periodicals, Inc.